Eksistensi Tradisi Menyilaq pada Masyarakat Suku Sasak di Tengah Gempuran Teknologi Informasi Modern - Suhadah Suhadah; Fathurrijal Fathurrijal; Cucu Cahyanti; Baiq Ida Astini (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2026)
The rapid development of modern information technology has transformed human communication from face-to-face interactions to mediated digital relations. This study aims to examine the existence of the "menyilaq" tradition (oral invitation) among the Sasak people in Lombok, West Nusa Tenggara, amid the massive use of smartphones. Using a qualitative approach, data were gathered through observation, documentation, and in-depth interviews with cultural figures, community leaders, and local youths across Mataram, Central Lombok, East Lombok, and North Lombok. The analysis followed the qualitative interactive model of Miles, Huberman, and Saldana. The findings indicate that while the core values of "adab" (ethics) and emotional attachment persist, the execution of menyilaq has underwent a significant shift toward hybridization. In urban areas like Mataram, digital invitations via WhatsApp have largely substituted the conventional method due to efficiency. Conversely, in traditional communities such as Bayan (North Lombok), the face-to-face practice remains mandatory for sacred rituals. The study concludes that the community mitigates cultural erosion by adopting a "Hybrid-Pesilaq" model, which integrates practical technology with traditional communication ethics to maintain social harmony.